Evaluation of the Impact of the Public-Private Partnership Program in Economic Infrastructure Development (Journal of Economic Growth and Development Review, 2025)
This study examines the impact of Public-Private Partnership (PPP) programs on economic infrastructure development in Indonesia using a mixed methodological approach and a multi-dimensional evaluation framework. Based on an analysis of 30 PPP projects implemented during the period 2010-2023, the study finds that the PPP model produces an average cost efficiency of 17.3% higher and project completion is 22% faster than conventional procurement. Econometric analysis confirms a significant positive correlation between PPP investment and regional economic growth with an elasticity coefficient of 0.28 ( p
Keywords: Public-Private Partnership (PPP); Economic Infrastructure; Impact Evaluation; Value for Money; Governance; Sustainable Development; Regional Development; Indonesia